Bibliometric analysis of ecocentrism: Perspective on sustainable development and addressing environmental issues - Setiawan, Chandra Egy (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Ecocentrism, emphasizing the intrinsic value and interconnectedness of nature, has become a significant perspective in environmental and development fields. This article aims to explore research trends on ecocentrism using a science-mapping approach. Methods: A bibliometric analysis of 1,317 documents from Scopus (1982–2024) was conducted using VOSviewer and Biblioshiny to visualize research linkages. Findings: Research on ecocentrism has grown exponentially since 2010, with a peak in 2022. Key topics in this field include ecocide, ecocriticism, rights of nature, future generations, indigenous peoples, and posthumanism, providing a foundation for future studies. Conclusion: Ecocentrism plays a pivotal role in sustainable development, focusing on ecosystem restoration, responsible management, and ecological sustainability while promoting the rights of future generations and strengthening indigenous conservation efforts. Novelty/Originality of the Study: This study provides a comprehensive mapping of research on ecocentrism, revealing its growing significance and key topics that are central to advancing future ecological research and sustainable development.